Amina residual na flotação catiônica reversa de minério de ferro - Geraldo Magela Braga Batisteli (2007)
This study investigated the possibility of recovering residual amine contained in the tailings pulp of the reverse cationic flotation process of iron ore. Tailings samples from SAMARCO were used for this purpose. These samples were collected and, later, kept under rest to promote the separation between the water and the solid particles. The water was used for determination of the residual amine concentration and for flotation tests. The residual amine concentration was determined through indirect quantitative analysis using a spectrophotometer. A desorption stage was used intending to increase the residual amine concentration in the tailings pulp. The flotation tests were performed using, separately, the tailings waters and a composition of the same. A specific procedure to avoid the addition of water containing residual amine during theconditioning of the pulp with starch was developed for these tests. The iron ore used was collected from the SAMARCO flotation circuit feed. Several flotation tests using distilled water were performed. The results of these tests were used for comparison with the results of the tests performed with the tailings waters. The residual amine concentration of three out of four collection points was below the detection limit in thesampling performed in September of 2006. This result shows that, currently, there is not excess of amine dosage in the initial stage of the flotation process. For the flotation tests using tailings waters, involving a grinding stage prior to flotation, the concentrate always presented higher silica grades. These results were achieved using tailings waters from the flotation stages large volume cells and columns. The residual amineconcentration increase through the desorption stage, independently of pH, was not satisfactory. The present study concluded that the residual amine recovery contained in the tailings pulp of the reverse cationic flotation process of iron ore is possible, but its viability depends on the residual amine concentration and on quality of the water that contains the amine.